Piloting Kenya’s nature-based solutions monitoring & evaluation framework: Lessons from Chyulu Hills - Akoko, Tessie; Jalango, Dorcas; Binge, Brenda; Ngige, Chris (2026)
A pilot of Kenya’s emerging Nature-based Solutions (NbS) Monitoring & Evaluation (M&E) framework was implemented to address persistent fragmentation and inconsistency in measuring NbS outcomes, which had constrained evidence-based policy, investment decisions, and climate reporting. Led by the Ministry of Agriculture and Livestock Development (MoALD) with the Alliance of Bioversity International & CIAT, and supported by ICAT and UNEP Copenhagen Climate Centre, the pilot was conducted in the Chyulu Hills landscape. Data were collected in Kajiado and Makueni counties using different data instruments. Results indicated that NbS were already integrated into local livelihoods through soil and water conservation, agroforestry, pasture management, and nature-based enterprises (e.g., beekeeping and tree nurseries), though implementation quality and documentation remained uneven. The pilot demonstrated the importance of a harmonized indicator set spanning ecological condition, socio-economic outcomes, and governance to support consistent tracking, learning, and scaling of NbS impacts across Kenya.